A Study on Factors Influencing Road Traffic Accidents Including Survival Period of Victims, Mortality Pattern and Preventive Measures for Road Traffic Accidents (Medico Legal Update, 2019)
The term accident has been defined as an occurrence in a sequence of events which usually producesunintended injury, death or property damage. Today, accidents are among the leading causes of death. Thepresent study was conducted in the Department of Forensic Medicine at RNT Medical College, Udaipur.The major head injuries were seen in 154 (77.6%) cases. The skull fractures were seen in 87 cases (56.4%).Subdural haematomas were the most frequent intracranial haematomas seen in 24 cases (15.5%). Cervicalspine injuries were seen in 3 (1.5%) cases. In present study chest injuries were seen in 88 (44%) cases.Abdominal injuries were seen in 78 (39%) cases. The study was conducted to prevent road traffic accident.The time required for transport of victims to hospitals was between 1.5 to 3.5 hours. 38.5% deaths occurredwithin half an hour of the accident whereas about three quarter (77.1%) died within 12 hours.